Acellular human corneal matrix sheets seeded with human adipose-derived mesenchymal stem cells integrate functionally in an experimental animal model. (March 2015) - Alio del Barrio, Jorge L.; Chiesa, Massimo; Garagorri, Nerea; Garcia-Urquia, Nerea; Fernandez-Delgado, Jorge; Bataille, Laurent; Rodriguez, Alejandra; Arnalich-Montiel, Francisco; Zarnowski, Tomasz; Álvarez de Toledo, Juan P.; Alio, Jorge L.; De Miguel, Maria P.
Abstract: Purpose: To evaluate the in vivo biocompatibility of grafts composed of sheets of decellularized human corneal stroma with or without the recellularization of human adipose derived adult stem cells (h-ADASC) into the rabbit cornea. Methods: Sheets of human corneal stroma of 90 μm thickness were decellularized, and their lack of cytotoxicity was assayed. The recellularization was achieved by the injection of 2 × 10 5 labeled h-ADASC in the graft followed by five days of cell culture. The grafts were implanted in vivo into a stromal pocket at 50% depth. After a triple-masked three-month follow-up, the animals were euthanized and the biointegration of the graft, the viability of the stem cells and the expression of keratocan (human keratocyte-specific protein) were assessed. Results: The decellularized stromal sheets showed an intact extracellular matrix with a decellularization rate of 92.8% and an excellent recellularization capacity in vitro with h-ADASC. A complete and stable graft transparency was observed during the full follow-up, with absence of any clinical sign of rejection. The postmortem analysis demonstrated the survival of the transplanted human stem cells inside the graft and their differentiation into functional keratocytes, as assessed by the expression of human keratocan. Conclusions: We report a new model of lamellar keratoplasty that requires only a simple and safe procedure of liposuction and a donor allogeneic cornea to provide an optically transparent autologous stromal graft with excellent biocompatibility and integration into the host tissue in a rabbit model. Highlights: h-ADASC colonize decellularized human corneal stromal sheets in vitro. Decellularized human corneal stromal sheets with or without h-ADASC recellularization achieve excellent in vivo biointegration. h-ADASC survive and differentiate into corneal keratocytes in vivo inside the grafts. Optically transparent stromal grafts are obtained in vivo with decellularized human corneal stromal sheets.